2008
DOI: 10.1101/gad.1682108
|View full text |Cite
|
Sign up to set email alerts
|

BMP/SMAD1 signaling sets a threshold for the left/right pathway in lateral plate mesoderm and limits availability of SMAD4

Abstract: The left/right (LR) axial pathway establishes asymmetry in the patterning and morphogenesis of multiple internal organs, including the heart. In mammals, this pathway involves the breaking of molecular symmetry in or around the node, transfer of asymmetry information to the lateral plate mesoderm (LPM), propagation of molecular asymmetries throughout the LPM, and interpretation of these signals for proper organ morphogenesis (Nonaka et al. 2002). Recent experiments have demonstrated that the breaking of bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…In line with these observations are several previous studies on the competitive binding of Smad4 between pSmad1/ 5/8 and pSmad2/3. It was shown that pSmad1 inhibited TGF␤-ALK5/pSmad2 pathway, and overexpression of Smad4 reversed the inhibition completely, indicating a competition between pSmad2 and pSmad1 for limited amounts of their common transcriptional cofactor Smad4 (29). TGF␤ stimulation could result in a decrease in pSmad1/5-Smad4 complexes formed in response to BMP and an increase in pSmad2/3-Smad4 complexes (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these observations are several previous studies on the competitive binding of Smad4 between pSmad1/ 5/8 and pSmad2/3. It was shown that pSmad1 inhibited TGF␤-ALK5/pSmad2 pathway, and overexpression of Smad4 reversed the inhibition completely, indicating a competition between pSmad2 and pSmad1 for limited amounts of their common transcriptional cofactor Smad4 (29). TGF␤ stimulation could result in a decrease in pSmad1/5-Smad4 complexes formed in response to BMP and an increase in pSmad2/3-Smad4 complexes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Activin/nodal ligands induce activation of Smad2 and Smad3. It was also reported that BMP and activin/nodal signaling pathways antagonize each other through competition between Smad1 and Smad2 for their binding to the common component Smad4 (29,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, competition between BMP-activated Smads and TGF-␤/activin Smads may control Nanog expression (35). This antagonism may be explained by competition for Smad4 (57) or heteromeric Smad combinations in transcription regulation (64). How Smad2 represses BMP signaling in the control of stem cell pluripotency remains to be further defined.…”
Section: Smad2 Controls Pluripotency and Nanog Expression-inmentioning
confidence: 99%
“…Chordin and noggin, which are BMP signaling antagonists, promote Nodal signaling around the node, while BMP signaling represses Nodal expression in the left LPM. 52, 53 The Nodal signaling pathway is mediated by an activin receptor complex composed of a dimmer of the type I activin receptor, ActRIB, and a dimeric type II receptor, Act-RII or ActRIIB. 54 Different from conventional Activin signaling, the Nodal pathway requires activities of membrane-bound EGF-CFC co-receptors, Cripto and Cryptic.…”
Section: Asymmetry Signaling Transmits To the Left Lpm And Upregulatementioning
confidence: 99%